Methodical approaches to the transition of the system of municipal diagnostic centers on principles of state-private partnership - Kravchenko, V. V. (Journal of Education, Health and Sport, 2017)
Introduction The need to attract private investment in the public health sector is one of the urgent problems in the Ukrainian health care system. Purpose: to substantiate methodological approaches to the transition of the municipal consulting and diagnostic centers (CDC) to the principles of public-private partnership (PPP). Materials and methods General scientific methods of analysis, synthesis, generalization, interpretation of scientific data, as well as systemic and structural-functional approaches were applied. Results A comprehensive analysis of the activities of municipal CDCs, as well as the prerequisites and risk factors for the introduction of PPPs, made it possible to obtain methodological material for the transition of CDC to the principles of PPP. Conclusions Presented in the article the methodical approaches to the organization of a modern model of a consultative and diagnostic center on the principles of PPPs are the way of adaptation of the communal CDC system to the conditions of a market economy.